Laparoscopic detorsion and fertility preservation in twisted ischemic adnexa - A single-center prospective study - Devi Balasubramaniam; Kavitha Yogini Duraisamy; Malathi Ezhilmani (Wolters Kluwer Medknow Publications, 2020)
Objective: This study aimed to analyze our experience about the salvageability of ovary in cases of adnexal torsion by laparoscopy, irrespective of the grade of necrosis and number of twists, and to assess the subsequent ovarian viability. Materials and Methods: This is a prospective study conducted in a tertiary care laparoscopic institute. All the cohorts of intraoperative diagnosis of adnexal torsion were included irrespective of the age group from January 2015 to January 2018 over the period of 3 years after obtaining approval from the institute's human ethics committee. Their demographic details and clinical and operative findings were entered after obtaining an informed written consent. All patients underwent laparoscopy except those with a suspicious diagnosis of malignancy. Postoperatively, ovarian viability was assessed by ultrasound Doppler in terms of vascularity and follicular development at 1, 6, and 12 months. Results: A total of 84 patients were included in the study. Acute abdominal pain (71.4%) was the main presenting symptom in all age groups. The total number of cases of adnexal torsion was 69. Adnexal torsion was mainly diagnosed in young and adolescent girls. Out of 46 attempted detorsion, 45 ovaries were preserved (97.8%). Most of the pathologies were benign. All the preserved ovaries were showing follicles and vascularity during ultrasound follow-up. Conclusion: Laparoscopic detorsion of the ovary is the best treatment modality irrespective of the grade of ischemia. Ovarian structure and follicles were preserved following detorsion in all the cases, even in gravely ischemic ovaries.